The Effects of Vertical Sleeve Gastrectomy in Rodents Are Ghrelin Independent - Chambers, Adam P.; Kirchner, Henriette; Wilson–Perez, Hilary E.; Willency, Jill A.; Hale, John E.; Gaylinn, Bruce D.; Thorner, Michael O.; Pfluger, Paul T.; Gutierrez, Jesus A.; Tschöp, Matthias H.; Sandoval, Darleen A.; Seeley, Randy J. (Gastroenterology (New York, N.Y. 1943), 2013)
Reductions in levels of the hunger-stimulating hormone ghrelin have been proposed to mediate part of the effects of vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass surgeries for obesity. We studied circulating levels of acyl and desacyl ghrelin in rats after these surgeries. We found that blood levels of ghrelin were reduced after VSG, but not after Roux-en-Y gastric bypass, based on enzyme-linked immunosorbent assay and mass-spectrometry analyses. We compared the effects of VSG in ghrelin-deficient mice and wild-type mice on food intake, body weight, dietary fat preference, and glucose tolerance. We found that VSG produced comparable outcomes in each strain. Reduced ghrelin signaling therefore does not appear to be required for these effects of VSG.